Problems Scanning Related to Stunting Using Iceberg Theory Model in Salakbrojo Village Central Java - Yuniarti Yuniarti; Ristiawati Ristiawati; Dewi Nugraheni Restu Mastuti; Muhammad Fatih (Faculty of Public Health, Hasanuddin University, Makassar, 2024)
The prevalence of stunting to date is 21,6%, which is far from target which is 14%. Research aimed to elaborate on problem of stunting using iceberg method model analysis. The research is a qualitative study with a phenomenological approach to obtain idea of stunting occurrence pattern as well as the root of problem. Data was collected by assigning focused group discussion. Correspondents were ten mothers of toddlers, five health cadres, a secretary of rural, and a rural midwife. Validity test was done by doing data source triangulation during focused group discussions. Mental model analysis was taken using directly elicited mental model technique by doing content analysis. Result of iceberg analysis found that occurrence of stunting was 3,42%. Patterns and trends include wasting 2,92%, normal nutrition 84,39%, risk of overnutrition 5,85%, overnutrition 1,95%, and obesity 1,46%. Systemic structure has shown there are relation between direct cause include lack of food intake, exclusive breastfeeding, complementary food, infectious diseases and incomplete basic immunization. Indirect causes for stunting include lack of knowledge of stunting, access of health services, house condition triggers infectious diseases and poor sanitation. The mothers’ analysis on mentality who are confident about their children being healthy and active despite nutritional problems. Mental model of health cadres, rural midwives, rural government and public health centers believe that collaboration in solving stunting problems is needed. It can be concluded that iceberg model can be applied in analyzing stunting problem and results of it can be considered in the implementation of stunting treatment.